2012
DOI: 10.1002/ls.1181
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of flexible multirecess hydrostatic journal bearing operating with micropolar lubricant

Abstract: This paper presents the analytical study of the effect of the bearing shell flexibility on the performance of multirecess hydrostatic journal bearing system operating with micropolar lubricant. The modified Reynolds equation for the flow of micropolar lubricant through constant flow valve‐compensated hydrostatic journal bearing has been solved by finite element technique based on Galerkins method, and the resulting elastic deformation in the bearing shell due to fluid‐film pressure has been determined iterativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Geometric and operating parameters for conical journal bearing system. [7][8][9][13][14][15][16][17][18]20,19 Bearing aspect ratio (λ) 1 Figure 3. Variation of maximum fluid-film pressure (p max ) versus radial load W r À Á .…”
Section: (A) Radial Load Capacity ( ) Vs Radial Eccentricity Ratio (mentioning
confidence: 99%
See 2 more Smart Citations
“…Geometric and operating parameters for conical journal bearing system. [7][8][9][13][14][15][16][17][18]20,19 Bearing aspect ratio (λ) 1 Figure 3. Variation of maximum fluid-film pressure (p max ) versus radial load W r À Á .…”
Section: (A) Radial Load Capacity ( ) Vs Radial Eccentricity Ratio (mentioning
confidence: 99%
“…In recent years, many investigators [13][14][15][16][17] studied the effect of micropolar lubrication on the performance of different types of fluid-film bearings such as hydrodynamic journal bearing, step bearing and lobbed hydrodynamic bearing. The studies 18,19 dealt with the influence of micropolar lubrication on the performance of hydrostatic and hybrid journal bearing. The studies [13][14][15][16][17][18]20,19 indicate that the use of micropolar lubricant results in a significant enhancement in the performance of the bearing system vis-à-vis Newtonian lubricant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of orifice compensated non-recessed hole-entry hybrid journal bearing operating with micropolar lubricants was done by Ram et al [10] to obtain optimum values of fluid film stiffness coefficients. Verma et al [11,12] analyzed and compared performance characteristics of flexible multirecess capillary and CFV compensated hydrostatic journal bearing operating with micropolar lubricant and observed a significant influence of bearing shell flexibility and micropolar effect on bearing performance. Recent studies on journal bearings operating with micropolar lubricant by Ram et al [13] and Rana et al [14] demonstrated the influence of micropolar parameters on performance characteristics of journal bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, the time‐dependent Reynolds equation and the flow equation must be solved by applying the finite difference method or the finite element method to obtain the dynamic pressure and the dynamic force. Additionally, the stiffness and damping coefficients of the hydrostatic bearing are obtained by expanding the Taylor series of the oil film force of the bearing in the steady‐state equilibrium position . However, the influence of fluid compressibility on stiffness and damping is not taken into account in these papers.…”
Section: Introductionmentioning
confidence: 99%